SPIROHYDANTOINS OF GLUCOFURANOSE - ANALOGS OF HYDANTOCIDIN - Brandstetter, T; Kim, Y; Son, J; Taylor, H; Lilley, P; Watkin, D; Johnson, L; Oikonomakos, N; Fleet, G (1995)
Routes from both γ- and δ-glucoheptonolactones to spirohydantoins of glucofuranose are described, affording further analogues of hydantocidin. It may be that the glucofuranose isomers are more stable than the glucopyranose forms. © 1995.